Nanomaterials for Biocatalysis - Castro, Guillermo R. (Micro & nano technologies., 2022)
Nanomaterials for Biocatalysis explains the fundamental design concepts and emerging applications of nanoscale biocatalysts, such as bioconversions, bioelectronics, biosensors, biocomputing and therapeutic applications. Nano-biocatalysts refers to the incorporation of enzymes into nanomaterials. These enzyme-enhanced nanocarriers have many advantages, including low mass transfer limitation, high enzyme capacity, better stabilization, and the formation of single-enzyme nanoparticles. Smart nanocontainers have been developed for the smart release of their embedded active substances. These smart releases can be obtained by using smart coatings as their outer nanoshells. In addition, these nanocontainers could protect the enzymes from chemical or metabolic alterations on their delivering pathways towards the target. This is an important reference source for materials scientists and chemical engineers who want to know more about how nanomaterials are being used for biocatalysis applications.